Commentary on the Right to Education: An Expository of Article 12 of the Maputo Protocol - Onuora-Oguno, Azubike (Public Governance, Administration and Finances Law Review, 2023)
The right to education is identified as a crucial and classical right. This classification is premised on the fact that it provides the basis on which an individual has the potential to transform their status and build their desired personality. Additionally, it is the basis on which society is projected to be transformed and set on a better pedestal, with individuals playing positive roles. The recognition of the right, though emanating from the Universal Declaration of Human Rights (UDHR) received only tacit recognition through other treaties. The Maputo Protocol recognises the right to education, as it flows from the African Charter on Human and Peoples’ Rights. This commentary, therefore, examines the right to education as enshrined in the Maputo Protocol with the aim of restating the grounds covered in the protection of female children and women and exposing lost opportunities. Finally, it makes recommendations on how the lost ground can be covered and give better content and scope to the right to education.